Promoting food security and sustainable agriculture through facilitated access to plant genetic resources for food and agriculture - Naluwairo, Ronald; Tabaro, Edgar (Advocates Coalition for Development and Environment ACODE, 2006)
The International Treaty on Plant Genetic Resources for Food and Agriculture (herein after referred to as the Treaty) is a landmark international agreement for ensuring food security and sustainable agriculture especially in the developing countries. It establishes an elaborate system of facilitated access to a number of plant genetic resources considered key in agriculture production and meeting the nutritional and food related needs of humanity. Under the system, access is to be provided expeditiously with minimal costs, if at all, only to cover the administrative costs involved. The system also offers several monetary and non-monetary benefits that are vital for ensuring sustainable agriculture, and increased and improved food production to feed the rapidly growing world population.